A new faith and a new name? Crusades, conversion, and baptismal names in medieval Baltics. Issue 2 (2nd April 2016) - Selart, Anti
ABSTRACT: The baptism of the natives in Estonia and Latvia in the thirteenth century did not result in compulsory name change. The native population accepted the "Christian" names by the mid-sixteenth century as a result of general cultural adaption of elements of the "German" culture of socially higher classes, but this process does not directly reflect the process of acceptance of the Christian religion. The few examples of receiving a new name in the crusading period indicate the re-arrangement of political relations, which were related to creating patronage ties and god-parenthood relations.